Раннетрипольское святилище в Сабатиновке II. Проблема интерпретации строительных остатков триполья - Бурдо, Н.Б. (Археологія і давня історія України, 2018)
На основании полевой документации, а также
материалов, хранящихся в Научных фондах Института археологии НАН Украины, детально рассмотрены данные для реконструкции постройки,
широко известной как «святилище на раннетрипольском поселении Сабатиновка II» в Кировоградской обл. Предложена реконструкция сооружения,
основанная на фактическом материале. The remains of three burnt mud houses and one depression were investigated at Trypillia A site Sabatynivka II.
Particular interest in this explorations was attracted by findings related to the sacred practice, namely by famous
M. L. Makarevych’s reconstruction of the dwelling 3 as a sanctuary. During the last 50 years, the graphic reconstruction
of this object was used many times by different authors without a slightest attempt of its verification.
The article analyzes the data for the reconstruction of the sanctuary at the early settlement of Sabitatynivka II
in the Kirovohrad region. The analysis of field documentation and the description
of the excavation of dwelling 3 in Sabatynivka II from all available sources reveals some inconsistencies in the real
object and details reconstructed by various researchers. The fact that the object is partially destroyed by the late
trench makes it difficult to reconstruct and interpret it. Turning to the possible reconstruction of this building, the
obvious traces of the ritual fire in which the building died should be noted. The obtained data suggest that the dwelling
3 was a rectangular adobe two-storey building. Most of the items found during excavations, including numerous
figurines, are connected to the second floor. The ritual character of the fire is indicated by the inventory placed in
the house before burning. However, there are no grounds for the reconstruction of the furnace, the elevation-altar
and clay chair, as well as the «ritual of baking bread» in this house.